2017
DOI: 10.4174/astr.2017.93.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3 fatty acids inhibit oxidative stress in a rat model of liver regeneration

Abstract: PurposeLipid peroxidation and consequent reactive oxygen species in the setting of oxidative stress have crucial roles in liver regeneration, which may adversely affect the regeneration itself and lead to liver failure. The aim of the current study is to investigate whether omega-3 fatty acid supplementation inhibits oxidative stress in an experimental model of liver regeneration.MethodsForty rats were allocated to four groups. Rats in group A received a sham operation. Rats in group B were subjected to right … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 30 publications
2
14
0
1
Order By: Relevance
“…However, in the lean rats, dietary hemp seed oil was even able to favorably increase the hepatic ratio of GSH/GSSG, suggesting that PUFAs can have positive effects on the antioxidant status, if not disturbed by an obesogenic state. This seems to be in agreement with Firat et al [37], who observed an inhibition of oxidative stress in rat livers by omega-3 fatty acids.…”
Section: Discussionsupporting
confidence: 93%
“…However, in the lean rats, dietary hemp seed oil was even able to favorably increase the hepatic ratio of GSH/GSSG, suggesting that PUFAs can have positive effects on the antioxidant status, if not disturbed by an obesogenic state. This seems to be in agreement with Firat et al [37], who observed an inhibition of oxidative stress in rat livers by omega-3 fatty acids.…”
Section: Discussionsupporting
confidence: 93%
“…The molecular mechanism may involve the increase of Nrf-2 in the nucleus and be correlated with cell proliferation. Firat et al reported the negative impact of oxidative stress via the production of ROS in cell proliferation, mainly due to the arrest of cell growth and activation of proteins that inhibit the cell cycle [54]. They found that the omega-3 parenteral administration to Wistar rats with right portal vein ligation, can reduce the levels of nitric oxide (NO) and ROS, with an increase in glutathione peroxidase and reduced glutathione (GSH), among other antioxidants' systems of defense, improving the system of regeneration in the contralateral lobe [54].…”
Section: Discussionmentioning
confidence: 99%
“…Fish oil contains a high concentration of omega-3 polyunsaturated fatty acids. Omega-3 fatty acids and their longer-chain downstream products, such as eicosapentaenoic acid (EPA), docosapentaenoic acid, and docosahexaenoic acid (DHA) have been reported to be beneficial in models of critical illness (Firat et al, 2017). The effects of omega-3 fatty acids include modulation of the immune response, inhibition of proinflammatory factors, and promotion of anti-inflammatory mediators.…”
Section: Introductionmentioning
confidence: 99%